2003
DOI: 10.1002/er.946
|View full text |Cite
|
Sign up to set email alerts
|

Chemical effects of CO2 addition to oxidizer and fuel streams on flame structure in H2-O2 counterflow diffusion flames

Abstract: SUMMARYNumerical simulation of CO 2 addition effects to fuel and oxidizer streams on flame structure has been conducted with detailed chemistry in H 2 -O 2 diffusion flames of a counterflow configuration. An artificial species, which displaces added CO 2 in the fuel-and oxidizer-sides and has the same thermochemical, transport, and radiation properties to that of added CO 2 , is introduced to extract pure chemical effects in flame structure. Chemical effects due to thermal dissociation of added CO 2 causes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 18 publications
0
38
0
Order By: Relevance
“…The study of Feese and Turns might pass over the fact that the strain rate varied while they maintaining the fixed nozzle exit velocities or the fixed mass fluxes. The explanation with a characterized strain rate (Park et al, 2003b) might ignore the difference in fuel-and oxidizer-side boundary conditions; that with flame location (Park et al, 2003c) described NO emission behaviour well with the propriety of flow residence time according to the distance from the stagnation point to the flame location, even if it is not a basic answer. This may imply that even chemical reaction effects should also be affected by relative flame location to the stagnation point.…”
Section: Introductionmentioning
confidence: 96%
“…The study of Feese and Turns might pass over the fact that the strain rate varied while they maintaining the fixed nozzle exit velocities or the fixed mass fluxes. The explanation with a characterized strain rate (Park et al, 2003b) might ignore the difference in fuel-and oxidizer-side boundary conditions; that with flame location (Park et al, 2003c) described NO emission behaviour well with the propriety of flow residence time according to the distance from the stagnation point to the flame location, even if it is not a basic answer. This may imply that even chemical reaction effects should also be affected by relative flame location to the stagnation point.…”
Section: Introductionmentioning
confidence: 96%
“…showing a well-known C-curve. The decrease of maximum flame temperature at low global strain rates is due to flame radiation (Park et al, 2003;2005;Ju et al, 1997). It is also shown that the global strain rate at the maximum of maximum flame temperature shifts to lower one as X CH 4 decreases.…”
Section: Numerical Strategies and Methodsmentioning
confidence: 89%
“…The increase of the forward reaction rate is relevant to the remarkable formation of H atom, despite of the decrease of methane mole fraction. It has been also well known that the populations of the chain carrier radicals (H, O, and OH) increase with the increase of strain rate (Park et al, 2003). Figure 5 shows the variation of maximum (a) CO and (b) CO 2 mole fractions with global strain rate for various blended fuels with hydrogen and methane.…”
mentioning
confidence: 95%
“…Subsequently the existence of hydrocarbon products inhibits chain branching since the rate of the major chain branching reaction, H+O 2 =O+OH, is much less than the rate of reaction between H atoms and hydrocarbons, so that the major chain branching reaction, H+O 2 =O+OH, is prohibited. Recent researches on the chemical effects of carbon dioxide addition to both the fuel-and the oxidizer-sides of a diffusion flame (Liu et al, 2001;Park et al, 2003) displayed that the reaction CO 2 +H->CO+OH was found to be the major starting point of the chemical effects of added CO 2 , and the chemical effects of added CO 2 were also seen to suppress NO x formation. Park et al, (2003) also recognized that the reason why flame temperatures with CO 2 addition to the fuel-side were lower compared with those with CO 2 addition to the oxidizer-side was closely associated with a characterized strain rate, and the chemical effects were much more prevailing with CO 2 addition to the oxidizer-side.…”
Section: Introductionmentioning
confidence: 95%